Tinjauan Filosofis Dalam Hadis Tentang Nikah Siri Dalam Hukum Islam Di Indonesia - Nur Ainun Mardiah (Al-Hasyimi: Jurnal Ilmu Hadis, 2025)
Nikah Siri refers to a form of marriage conducted in accordance with Islamic law but not officially registered with the state, thereby lacking legal recognition under positive law. Although it fulfills the essential elements of Islamic jurisprudence such as the presence of a guardian (wali), witnesses, consent (ijab qabul), and dowry (mahr) the absence of public announcement (i’lan) and state registration leads to significant legal, social, and psychological consequences, particularly for women and children. This study aims to provide a philosophical analysis of the Nikah Siri practice through the lens of Hadith and the Maqasid Shariah framework, to assess its alignment with the fundamental objectives of Islamic law. Utilizing a qualitative method and library research approach, this study analyzes primary sources such as the Quran, Hadith, and statutory regulations (Law No. 1 of 1974, the Compilation of Islamic Law, and Law No. 16 of 2019), as well as relevant secondary literature. The findings reveal that while Nikah Siri may be deemed valid from a formal fiqh perspective, it fails to uphold the core objectives of Maqasid Shariah, particularly in safeguarding lineage (hifz al-nasl), dignity (hifz al-‘irdh), and property (hifz al-mal). The lack of official registration results in unclear legal status for marriages and offspring, deprives women of legal protection, and jeopardizes economic and social rights. Consequently, Nikah Siri not only generates juridical disadvantages but also contradicts the ethical and social goals of Islamic law. These findings advocate for enhanced legal education and the harmonization of religious norms with state regulations as strategic measures for protecting Muslim families.